Finding studies on reboxetine: a tale of hide and seek. (12th October 2010) - Wieseler, Beate; McGauran, Natalie; Kaiser, Thomas
Abstract : Beate Wieseler, Natalie McGauran, and Thomas Kaiser use their experience with the assessment of reboxetine to illustrate how publication bias affects health policy decisions and offer some solutions